HUBUNGAN TINGKAT PENGETAHUAN DAN PEKERJAAN KEPALA KELUARGA DENGAN TINGKAT PARTISIPASI DALAM PELAKSANAAN PROGRAM BANK SAMPAH (Studi Dilaksanakan di Desa Sebatu Kecamatan Tegallalang Kabupaten Gianyar Tahun 2022 - Ni Kadek Heni Sonia; I Ketut Ketut Aryana; I Wayan Wayan Jana (Poltekkes Kemenkes Denpasar, 2022)
PP Number 81 of 2012 concerning Management of Household Waste and Waste Similar to Household Waste mandates a fundamental paradigm shift in waste management, namely from the collect - transport - throw away paradigm to Reuse, Reduce, Recycle (3R). The purpose was to determine the relationship between the level of knowledge and occupation of the head of the family with participation in the waste bank program. This research is a type of descriptive research with a quantitative approach using a cross sectional with the sample of 95 head of the family as with the instrument used is a questionnaire. The analysis was carried out by univariate and bivariate with chi square. Based on hypothesis testing, it is known that the level of knowledge and the work of the head of the family with the level of participation in the waste bank program gets a P-value = 0.010 0.05, P-Value = 0.000 0.05. So it can be concluded that there is a relationship between the level of knowledge and work of the head of the family with the level of participation in the waste bank program in Sebatu Village. The advice that can be given is expected that all Heads of Families can participate in this waste bank program, provide socialization about the waste bank program, hold programs in waste banks and the government provides allocation of funds for waste banks to run in accordance with their functions.